Integração de um sistema de recomposição automático via OPC para automação da rede elétrica de distribuição em média tensão do campus do Pici da Universidade Federal do Ceará - Santos, Lucélia Alves dos (2015)
For a long time the maintenance of the power distribution system of the Pici Campus of the Federal University of Ceará - UFC was the responsibility of the Energy Company of Ceará - Coelce, by the partnership between the federal and state governments. However, with the privatization of Coelce in 1998, the UFC assumed that demand and for many years, due to lack of resources and planning, only the emergency and corrective interventions have taken place, thereby have emerged several problems in continuous supply. Fortunately, the last managers have paid attention to the problem and many investments in the medium voltage distribution network are being carried out, aimed at modernizing and improving security, availability and continuity of energy supply of Pici campus. These actions were based on technical studies conducted by the Department of Electrical Engineering in partnership with the engineering sector of the UFC (UFC-Infra). In this context, was designed and is being implemented a power substation of 69 to 13.8 kV, with two transformers of 5 / 6.25 MVA, , three outputs feeders and nine reclosers distributed throughout the medium voltage distribution network of the campus. This system will be operated, supervised and controlled by a SCADA system (Supervisory Control and Data Acquisition), developed in the commercial platform Elipse Power using the Microsoft® SQL Server 2012 database - Express version. In the field of automation, it was developed and integrated into the SCADA via OPC (Open Communications Platform), an advanced function called Automatic Restoration System (ARS-PICI). The ARS-PICI was developed in C # using Microsoft Visual Studio 2010 program, modelled on Colored Petri Nets, and tested using the CPN Tools analysis program. For integration of the SCADA and the ARS application software was used the OPC open protocol that specifies the real time data communication between a source element and a receiving element from different manufacturers. Validation tests of the ARS and communication between the software SCADA-ARS were performed in the laboratory, attesting to the successful implementation and opening important perspectives to advance toward a smart grid to the campus of the Pici.